Предмет: Алгебра,
автор: jalgashevsaidkarim
621)упростите . (a+3)2+(a-3)2. 2) (4a+b)2-(4a-b)2
Ответы
Автор ответа:
1
Ответ:
ab-4a=a(b-4)
a=2, b= -1
2*( -1 - 4)= - 2*5= -10
2a+3ab=a(2+3b)
a= -1, b=0
-(2+3*0)= - 2
ba-3a+1=a(b -3+1)=a(b-2)
a=1, b=2
2-2=0
2ab+3b -1=b(2a+3)-1
a=2, b= -1
-1*(2*2+3) -1= - 8
a-4ab+2=a(1-4b)+2
a=0, b= -3
0*(1-4b)+2=2
a+2b -ab=a(1-b)+2b
a=1, b= -3
(1+3) -2*3=4-6= -2
ab-4a -2b=b(a-2) -4a
a=4, b= -1
-(4-2) -4*4= - 2 -16= -18
a+ab+b=a+b(a+1)
a=1, b= -1
1 - (1+1)= -1
Объяснение:
aligyurgaz:
оффф ну вроде так
Похожие вопросы
Предмет: Русский язык,
автор: ЯиЧкИ1
Предмет: Русский язык,
автор: ваги1
Предмет: Английский язык,
автор: alinaashigova
Предмет: История,
автор: alina710
Предмет: Математика,
автор: TakhminaZh